Will Low-Carbon Purchasing Behavior Make Residents’ Behaviors Greener? Research Based on Spillover Effects - Yue, Ting; Zhang, Lan; Long, Ruyin; Chen, Hong; Gao, Chenchen; Li, Mengting (Frontiers in Environmental Science, 2021)
Low-carbon purchasing behavior is the core part of low-carbon consumption behavior. Its impact on low-carbon use behavior, recycling behavior, and garbage sorting behavior needs to be further clarified. Based on self-perception theory and cognitive dissonance theory, this paper constructs a theoretical model of the spillover effect of low-carbon purchasing behavior on low-carbon use behavior, recycling behavior and garbage sorting behavior through self-efficacy and environmental self-identity. This paper uses the Bootstrap method to analyze 494 valid questionnaires empirically. The results show that: low-carbon purchasing behavior has a significantly positive effect on low-carbon use behavior, recycling behavior, and garbage sorting behavior. Self-efficacy and environmental self-identity play partially parallel mediating roles in the spillover effect. The mediating effect of environmental self-efficacy is stronger than environmental self-identity between low-carbon purchasing behavior and low-carbon use behavior. The mediating effect of self-efficacy is weaker than environmental self-identity between low-carbon purchasing behavior and recycling behavior or garbage sorting behavior. The spillover effects are different in demographic variables. The spillover effect of men is more substantial than women. The spillover effect of residents in18-44 years old is more significant than residents in other age groups. The spillover effect of married residents is the largest. Residents with a bachelor’s degree have the most significant spillover effects on recycling behavior and garbage sorting behavior than residents with other educational levels. Professional and technical personnel have the most considerable spillover effect than other occupation types. The spillover effect is the largest when the family have three members. The spillover effect of residents with a monthly household income of 6,000-8,000 yuan is the largest between low-carbon purchasing behavior and low-carbon use behavior.